Prediction of Blood Pattern in S-Shaped Model of Artery under Normal Blood Pressure - Mohd Azrul Hisham, Mohd Adib; Norashikin, Nor Tuah; Nur Hazreen, Mohd Hasni; Kahar, Osman (Faculty Mechanical Engineering, UMP, 2013)
Athletes are susceptible to a wide variety of traumatic and non-traumatic vascular injuries to the lower limb. This paper aims to predict the three-dimensional flow pattern of blood through an S-shaped geometrical artery model. This model has created by using Fluid Structure Interaction (FSI) software. The modeling of the geometrical Sshaped artery is suitable for understanding the pattern of blood flow under constant normal blood pressure. In this study, a numerical method is used that works on the assumption that the blood is incompressible and Newtonian; thus, a laminar type of flow can be considered. The authors have compared the results with a previous study with FSI validation simulation. The validation and verification of the simulation studies is performed by comparing the maximum velocity at t = 0.4 s, because at this time, the blood accelerates rapidly. In addition, the resulting blood flow at various times, under the same boundary conditions in the S-shaped geometrical artery model, is presented. The graph shows that velocity increases linearly with time. Thus, it can be concluded that the flow of blood increases with respect to the pressure inside the body.